2012
DOI: 10.1289/ehp.1104349
|View full text |Cite
|
Sign up to set email alerts
|

Winter Temperature Inversions and Emergency Department Visits for Asthma in Salt Lake County, Utah, 2003–2008

Abstract: Background: Winter temperature inversions—layers of air in which temperature increases with altitude—trap air pollutants and lead to higher pollutant concentrations. Previous studies have evaluated associations between pollutants and emergency department (ED) visits for asthma, but none have considered inversions as independent risk factors for ED visits for asthma.Objective: We aimed to assess associations between winter inversions and ED visits for asthma in Salt Lake County, Utah.Methods: We obtained electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 21 publications
1
46
0
1
Order By: Relevance
“…The health condition may however be influenced by various seasonal changes. Several studies, with different strength of evidence, showed that some associations may exist between meteorological variables and different clinical conditions such as stroke [13], myocardial infarction [14], renal colic [15], atrial fibrillation [16], asthma [17], epistaxis [18], and arthritic pain [19]. Psychiatric emergencies are also influenced by climatic variables, although with variable degrees of strength and evidence [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The health condition may however be influenced by various seasonal changes. Several studies, with different strength of evidence, showed that some associations may exist between meteorological variables and different clinical conditions such as stroke [13], myocardial infarction [14], renal colic [15], atrial fibrillation [16], asthma [17], epistaxis [18], and arthritic pain [19]. Psychiatric emergencies are also influenced by climatic variables, although with variable degrees of strength and evidence [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Beard et al (2012) during winter seasons in Salt Lake County (USA) revealed an association between inversions and emergency visits to the hospital for asthma. Abdul-Wahab et al (2005) states that the daily average number of hospital visits in Oman increased with an increase in the inversion depth and strength of surfacebased inversions.…”
Section: Introductionmentioning
confidence: 99%
“…These elevated PM 2.5 levels cause adverse health effects locally. For example, the state of Utah found that the odds of an emergency department visit in Salt Lake County, with a primary diagnosis of asthma, are 42% greater during days 5-7 of prolonged inversions than for noninversion days (Beard et al, 2012). During a particularly extreme cold-air pool event in 2004, 24-hr average PM 2.5 concentrations exceeded 100 mg/m 3 (Malek et al, 2006), while more recent maximum daily average concentrations have been in the range of 50-70 mg/m 3 .…”
Section: Introductionmentioning
confidence: 99%